Cobalt-Promoted Dimerization of Aminoquinoline Benzamides - Grigorjeva, Liene (Org Lett, 2015)
A method for aminoquinoline-directed, cobalt-promoted dimerization of benzamides has been developed. Reactions proceed in ethanol solvent in the presence of Mn(OAc)(2) cocatalyst and Na(2)CO(3) base and use oxygen as a terminal oxidant. Bromo, iodo, nitro, ether, and ester moieties are compatible with the reaction conditions. Cross-coupling of electronically dissimilar aminoquinoline benzamides proceeds with modest yields and selectivities. [Image: see text]